(untitled) (FAVE Sección Ciencias Veterinarias, 2018)
The lactation curve can be defined as the expression of the productive behavior of the goat herd. Knowing it is a selection tool. The objective of this work was to study the productive behavior of Saanen goats under semi-intensive conditions using different mathematical models to describe their lactation curve, characterize the evolution of milk production and analyze the variation associated with lactation number and the kids size. Data records of 182 animals were used. From each animal, we recorded: calving number, litter size and the individual daily production from the third day after parity until the end of lactation (270 days). The Cappio-Borlino model was the best fit. When analyzing the results obtained regarding the moment in which the production peak is reached, it is observed that, in addition to being numerically smaller, the goats of first calving are the ones that show it later with respect to the multiparous. In turn, the animals with double births, although they presented a higher milk production at the beginning of the lactation, the persistence was lower than goats with triple births.